1997
DOI: 10.1021/ma961225q
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactivity of Polymers with Regioisomeric Cinnamate Side Chains and Their Ability To Regulate Liquid Crystal Alignment

Abstract: Photoproduct distribution in films of cinnamate polymers was analyzed to reveal the contribution of both photoisomerization and photodimerization to LC alignment photoregulation. A polymethacrylate with o-cinnamate side chains displayed preferential formation of Z-isomer while the dimerization takes place more favorably for other polymers including poly(vinyl cinnamate). On the basis of the relationship between photoproduct distribution and liquid crystal photoalignment and on the reversibility of the photoind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
183
2
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 250 publications
(193 citation statements)
references
References 25 publications
(75 reference statements)
6
183
2
2
Order By: Relevance
“…16 If the optical anisotropy continue to increase under a continuous UV irradiation, LC alignment can be observed to quite stable. In order to overcome these problems, we designed and synthesized the photoreactive main chain oligomer bearing the chalcone group in the repeating unit and epoxy groups in the terminal ends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 If the optical anisotropy continue to increase under a continuous UV irradiation, LC alignment can be observed to quite stable. In order to overcome these problems, we designed and synthesized the photoreactive main chain oligomer bearing the chalcone group in the repeating unit and epoxy groups in the terminal ends.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the photocrosslinkable side chain polymer bearing the cinnamates or chalcone group showed that the molecular orderness is reduced as the power of the UV light goes higher. 16,24 Although the irradiation continued longer subsequently, the order parameter of the chalcone-epoxy sample with photoinitiator decreased continuously to show high anisotropy.…”
mentioning
confidence: 99%
“…For instance, linearly polarized UV irradiation of thin films of poly (vinyl cinnamate) generates uniaxially oriented homogeneous alignment of nematic LCs. [3][4][5][6][7] This technique is of practical significance because of the applicability to rubbing-free LC-aligning films, which are inevitable materials in the fabrication of LC display devices.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the problems arising from rubbing, e.g., mechanical damage and the generation of dust and electrostatic charges, photoalignment induced by polarized UVirradiation has emerged as an attractive alternative. Three distinct material approaches have been demonstrated: axisselective degradation of polyimides, [22][23][24][25][26] cis-trans isomerization of azobenzenes, [27][28][29] and cycloaddition of cinnamates, [30][31][32][33][34] or coumarins. [35][36][37][38][39][40][41][42] Orientational order parameter values emulating those on rubbed polymer alignment layers have been realized via thermal annealing of films comprising p-conjugated polymers 43,44 and oligomers 39,40 on photoalignment layers.…”
mentioning
confidence: 99%
“…A coumarincontaining polymer was chosen for its superior thermal and photochemical stability without complication from photoinduced isomerization. 31,35 Specific objectives are identified as follows: (i) solvent-vapor annealing of conjugated oligomers into uniaxially oriented monodomain films; (ii) elucidation of how vapor absorption affects the vapor annealing process; (iii) lyotropic nematic mesomorphism as the driving force for solvent-vapor annealing; (iv) effectiveness of solvent-vapor annealing on photoalignment layers versus rubbed polyimide alignment layers, and that of solvent-vapor annealing versus thermal annealing on rubbed polyimide alignment layers; and (v) demonstration of uniaxially oriented monodomain films on plastic substrates.…”
mentioning
confidence: 99%